Shape‐Anisotropic Microembolics Generated by Microfluidic Synthesis for Transarterial Embolization Treatment. Issue 10 (10th February 2022) - Luo, Yucheng; Ma, Yutao; Chen, Zijian; Gao, Yanan; Zhou, Yuping; Liu, Xiaoya; Liu, Xuezhe; Gao, Xu; Li, Zhihua; Liu, Chuang; Leo, Hwa Liang; Yu, Hanry; et al.
Abstract: Particulate embolic agents with calibrated sizes, which employ interventional procedures to achieve endovascular embolization, have recently attracted tremendous interest in therapeutic embolotherapies for a wide plethora of diseases. However, the particulate shape effect, which may play a critical role in embolization performances, has been rarely investigated. Here, polyvinyl alcohol (PVA)‐based shape‐anisotropic microembolics are developed using a facile droplet‐based microfluidic fabrication method via heat‐accelerated PVA‐glutaraldehyde crosslinking reaction at a mild temperature of 38 ° C. Precise geometrical controls of the microembolics are achieved with a nearly capsule shape through regulating surfactant concentration and flow rate ratio between dispersed phase and continuous phase in the microfluidics. Two specific models are employed, i.e., in vitro decellularized rabbit liver embolization model and in vivo rabbit ear embolization model, to systematically evaluate the embolization behaviors of the nonspherical microembolics. Compared to microspheres of the same volume, the elongated microembolics demonstrated advantageous endovascular navigation capability, penetration depth and embolization stability due to their comparatively smaller radial diameter and their central cylindrical part providing larger contact area with distal vessels. Such nonspherical microembolics present a promising platform to apply shape anisotropy to achieve distinctive therapeutic effects for endovascular treatments. Abstract : Shape‐anisotropic microembolics are developed through a facile droplet‐based microfluidic technique using a heat‐accelerated crosslinking reaction. The PVA‐based microembolics with regular elongated shapes demonstrate superior embolization properties in three critical aspects, i.e., endovascular navigation, penetration depth, and embolization stability. Such a nonspherical platform presents a new perspective to apply shape anisotropy to achieve distinctive therapeutic effects for endovascular treatments.